2020
DOI: 10.3889/oamjms.2020.3790
|View full text |Cite
|
Sign up to set email alerts
|

Association between KLOTHO Gene G395A Polymorphism and Carotid Artery Calcification in regular Hemodialysis Patients

Abstract: BACKGROUND: The vascular calcification process in chronic kidney disease (CKD) is a complication caused by mineral and bone abnormalities and becomes the risk of cardiovascular disease and mortality in CKD patients. KLOTHO is an inhibitor of calcification and its expression has been observed to decrease in CKD patients. The KLOTHO gene G395A polymorphism is a genetic variation that is common in Asian populations and is associated with vascular dysfunction in hemodialysis patients. OBJECTIVE: The objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…( 16) In Indonesia, a prior investigation on the klotho G395A SNP in the Medan population revealed that the majority of participants (52.2%) had the GG genotype, followed by the GA genotype (43.5%), and the AA genotype (4.3%). (10) There was a link between the klotho G395A SNP and the occurrence of carotid artery calcification. (10) Conflicting finding was noted regarding the effect of G/A substitution on the expression of G395A in the promoter of the klotho gene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…( 16) In Indonesia, a prior investigation on the klotho G395A SNP in the Medan population revealed that the majority of participants (52.2%) had the GG genotype, followed by the GA genotype (43.5%), and the AA genotype (4.3%). (10) There was a link between the klotho G395A SNP and the occurrence of carotid artery calcification. (10) Conflicting finding was noted regarding the effect of G/A substitution on the expression of G395A in the promoter of the klotho gene.…”
Section: Discussionmentioning
confidence: 99%
“…(10) There was a link between the klotho G395A SNP and the occurrence of carotid artery calcification. (10) Conflicting finding was noted regarding the effect of G/A substitution on the expression of G395A in the promoter of the klotho gene. Nevertheless, the A allele had been reported to form fewer DNA-protein complexes compared to the G allele.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation